Optimization of ultra-high pressure extraction technology of polysaccharide from Dendrobium officinale and its antioxidant activities - MENG Ji-kun; ZHANG Nan; WU Hao; ZHANG Xiu-qing (Shipin yu jixie, 2023)
Objective: Optimizing the extraction conditions of polysaccharides from Dendrobium officinale under ultra-high pressure, improving the yield of polysaccharides, and studying its basic properties and antioxidant activity in vitro. Methods: Using D. officinale dry powder as raw material, orthogonal experiment was used to optimize the extraction conditions of polysaccharide from D. officinale by ultra-high pressure technology. The relative molecular weight and monosaccharide composition of polysaccharides extracted from D. officinale by traditional hot water extraction method and ultra-high pressure extraction method were determined, and their antioxidant activities in vitro were compared. Results: Under the optimal conditions of 200 MPa, solid-liquid ratio of 1∶25 （g/mL） and treatment time of 5 min, the polysaccharide yield of D. officinale was 33.3%, which was 128% higher than that of the traditional hot water extraction method. The protein content and relative molecular weight of the extraction method were decreased, while the mannose content was increased. The scavenging ability of DPPH and other free radicals was improved. Conclusion: The polysaccharide extracted from Dendrobium officinale under ultra-high pressure has high yield and good antioxidant activity in vitro.